Desarrollo de una plataforma web para recorridos virtuales 360° mediante la metodología RAD. Caso Grupo Inmobiliario Horizonte de la ciudad de Riobamba - Bonilla Cadena, Jhoselyn Andrea (2022)
Covid-19 pandemic declared in December 2019 transformed lifestyles around the world, schools, high schools, universities and companies had to close. Therefore, technology became people's best ally, first, new software was created for teleworking, and second, existing software was used for virtual education. An important area that has remained without technological progress is the real estate area. For this reason, a web platform for 360° virtual tours is being developed using RAD methodology for the Horizonte Real Estate Group in the city of Riobamba. In this way the proposed project focuses on the benefit of workers and users to promote the work, offering new technologies such as virtual tours implemented on a web page where the user is provided with a better view of the housing. For the virtual tours 360° photographs were taken of the properties available in the catalogues and for the software development methodology Rapid Application Development (RAD) was implemented in their four phases. Once the web system is implemented, it is evaluated by means of usability parameters, field observation and the application of SUS tests, to measure the users experience (UX) from the employees in charge of testing the system. With the test completed, the result obtained was 85.62 points out of 100, achieving an A grade in user satisfaction with the website and the insertion of virtual tours